Fundamentals of wavelets : theory, algorithms, and applications - Goswami, Jaideva C.; Chan, Andrew K. (Hoboken, N.J. : Wiley, 2011)
"Most existing books on wavelets are either too mathematical or they focus on too narrow a specialty. This book provides a thorough treatment of the subject from an engineering point of view. It is a one-stop source of theory, algorithms, applications, and computer codes related to wavelets. This second edition has been updated by the addition of: a section on "Other Wavelets" that describes curvelets, ridgelets, lifting wavelets, etc. a section on lifting algorithms Sections on Edge Detection and Geophysical Applications Section on Multiresolution Time Domain Method (MRTD) and on Inverse problems."--
Includes bibliographical references and index.
Keywords: Wavelets (Mathematics); Image processing; Electromagnetic waves; Boundary value problems